2000
DOI: 10.1080/713670164
|View full text |Cite
|
Sign up to set email alerts
|

Health risk aversion, health risk affinity, and socio-economic position in the USA: The demographics of multiple risk

Abstract: Understanding the distribution of behavioural risk factors in the population can improve health promotion. This article reports on a research project which analysed the distribution of numbers of behavioural risk factors among US adults, by race/Hispanic origin, sex, and age. Income, education, and region were examined as potential confounders in observed patterns.The Behavioral Risk Factor Surveillance System (BRFSS) data for 1993 were used to assess the distribution of numbers of risk factors, i.e. smoking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It's been hypothesized that the better‐educated are more efficient at processing information about the risks and benefits of seat belts, or that they may have lower rates of time or risk preference (Blomquist, , ; Hersch, ; Leigh, ; O'Conor, Blomquist, & Miller, ; Rogers, ). Others have suggested that lower seat belt use among low socioeconomic groups reflects a more general pattern of multiple risk behaviors, including risky driving (Wilson, ), and there is indeed evidence that individuals from lower socioeconomic strata are more likely to exhibit multiple risk behaviors (Berrigan et al., ; Hahn, Vesely, & Chang, ; Rogers, Hummer, & Nam, ). Still others have suggested that disadvantaged individuals may be less likely to invest in prevention, be more fatalistic and less likely to believe traffic accidents are preventable, or may use belts less often because their parents did so (Becker, ; Girasek, ; Shin, Hong, & Waldron, ).…”
Section: Introductionmentioning
confidence: 99%
“…It's been hypothesized that the better‐educated are more efficient at processing information about the risks and benefits of seat belts, or that they may have lower rates of time or risk preference (Blomquist, , ; Hersch, ; Leigh, ; O'Conor, Blomquist, & Miller, ; Rogers, ). Others have suggested that lower seat belt use among low socioeconomic groups reflects a more general pattern of multiple risk behaviors, including risky driving (Wilson, ), and there is indeed evidence that individuals from lower socioeconomic strata are more likely to exhibit multiple risk behaviors (Berrigan et al., ; Hahn, Vesely, & Chang, ; Rogers, Hummer, & Nam, ). Still others have suggested that disadvantaged individuals may be less likely to invest in prevention, be more fatalistic and less likely to believe traffic accidents are preventable, or may use belts less often because their parents did so (Becker, ; Girasek, ; Shin, Hong, & Waldron, ).…”
Section: Introductionmentioning
confidence: 99%
“…( 7,8 ) Differences in risk perception have been studied along lines of gender, race and ethnicity, nationality, and socioeconomic status, with risk areas ranging from environmental health to finance to automobile accidents. ( 9–14 )…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) Differences in risk perception have been studied along lines of gender, race and ethnicity, nationality, and socioeconomic status, with risk areas ranging from environmental health to finance to automobile accidents. (9)(10)(11)(12)(13)(14) The risk literature has not extensively considered risks generated specifically by activities that distinguish one culture from another. Such cases are in great need of study because cultural marginality can create an environment vulnerable to government control of the perceived risky behavior, without formal assessment of those risks.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue is that previous research has pointed out that risk aversion and risk affinity might vary substantially by ethnic background and socioeconomic position (Hahn et al, 2000). Cross-sectional data does not allow testing if the differences between two population groups are attributable to observed or unobserved variables.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%